The Law of Polygamy According to Fikih Lughowi (Study of the Letter Athaf in Surah An-Nisa Verse 3) - Mahmudin Hasibuan; Maulana Ibrahim Ritonga (Prodi Hukum Ekonomi Syari'ah STAIN Mandailing Natal, 2025)
The Quran, Surah An Nisa verse 3, is often used as a normative basis in discussions of polygamy law, particularly in relation to differences in understanding the meaning of the letter Athaf waw in the phrase matsna wa tsulatsa wa rubaa. These differences in linguistic interpretation have direct implications for determining the limit on the number of wives in Islam and have sparked debate among scholars. This study aims to analyze the meaning of the letter Athaf in QS. An Nisa verse 3 through a linguistic fiqh approach and explain its implications for the determination of polygamy law. The research method used is literature research with a qualitative descriptive approach, through Arabic linguistic analysis and tracing the views of classical and contemporary mufassir and fuqaha. The results show that the letter Athaf waw in the verse does not mean addition of numbers, but functions as a connecting choice that is limiting in nature. Therefore, polygamy in Islam is permitted with a maximum of four wives on the condition of fairness. This finding confirms that polygamy is limited and cannot be understood as unlimited freedom, while also reinforcing the importance of the linguistic fiqh approach as a methodological basis in istinbat al Ahkam in the study of islamic family Law.